CuOx nanotubes via an unusual complexation induced block copolymer-like self-assembly of poly(acrylic acid) - Liang, Yen Nan (2013)
Polyelectrolyte (PEL) mediated synthesis of functional inorganic nano-materials is attractive due to its versatility and compatibility inside aqueous media. Block copolymers are often employed to facilitate the formation of novel nanostructures. In this work, we report the synthesis of copper oxide (CuOx) crystals with an unexpected hollow nano-tubular morphology using only poly(acrylic acid) (PAA), i.e., a homopolymer. The quantification of the pH dependent binding limit of Cu2+ to PAA, which has often been given little emphasis previously, is found to be critical in understanding the formation mechanism of such nanotubes. Further quantification of the interdependent relationship of pH, α, and [Cu2+] : [COOH]0 using the pKa-α curves provided important insight. The formation of the CuOx nanotubes is believed to be due to an unusual copolymer-like self-assembly of PAA as a homopolymer in aqueous solution; caused by interactions between Cu2+ and charged PAA chains. Such a unique copolymer-like self-assembly behaviour of the PAA–Cu2+ complex manifests within a specific window of [Cu2+] : [COOH]0 ratio around the binding limit. Discussion is also carried out on the possibilities and potential limitations of applying this new concept to other PELs and metal ions.